Apneia obstrutiva do sono e prevalência de fatores associados em motoristas de ônibus coletivos de uma capital brasileira de médio porte - Soares, Bruna Argôlo (2019)
Obstructive Sleep Apnea Syndrome (OSAS) is a common, underdiagnosed disease, caused by recurrent collapse of the upper airways during sleep, with repetitive hypoxia, micro-awakenings, excessive daytime sleepiness, fatigue and increased cardiovascular morbidity and mortality. It is considered a public health problem, with the possibility of causing serious economic, family, social and health damage with an increased risk of accidents at home, at work and, especially, traffic. Objective: To analyze the prevalence of high risk of sleep apnea, excessive daytime sleepiness and associated factors in collective bus drivers traveling in Cuiabá, Mato Grosso. Methods: Observational, cross- sectional study carried out with 144 bus drivers. By means of structured and validated questionnaires, Epworth Sleepiness Scale (ESE) and Berlin Questionnaires (QB), demographic, socioeconomic, anthropometric, lifestyle, clinical, hemodynamic (blood pressure), excessive daytime sleepiness data were obtained. high risk of sleep apnea. Poisson regression was used to estimate the prevalence ratio and respective confidence intervals (95%). Results: 144 individuals were evaluated, all male, with a mean age of 45.3 years. predominance of race / brown color (61.1%), overweight in 77.1% (43.1% overweight, 34.0% with obesity), waist circumference (≥ 94 cm), waist-hip ratio (≥ 0.9) and neck circumference (≥40 cm) increased, respectively, by 59.7%, 61.1% and 45.8% sedentary lifestyle in 60.4%, smoking in 14.5%, consumption of alcoholic beverages in 53.4%, coffee in 90.2%, history of traffic accidents in 56.9%, arterial hypertension in 24.3%, self-reported diabetes and dyslipidemia, respectively in 8.3% and 6.2 %. The ESE and QB questionnaires revealed, respectively, excessive daytime sleepiness in 32.4%, and high risk of OSAS in 56.2% of drivers. Sleep apnea showed a significant association with arterial hypertension and increased waist circumference (≥ 94 cm). Excessive daytime sleepiness revealed an association with increased neck circumference (≥41 cm) and body mass index. Conclusion: Bus drivers in Cuiabá have a high prevalence of excessive daytime sleepiness, risk of sleep apnea and cardiovascular risk factors, conditions that can compromise the quality of life and work activity of this professional segment.